Transplant Experiments Point to Fire Regime as Limiting Savanna Tree Distribution - Stevens, Nicola; Archibald, Sally A.; Bond, William J. (Frontiers in Ecology and Evolution, 2018)
Plant species range shifts are predicted to occur in response to climate change. The predictions are often based on the assumption that climate is the primary factor limiting the distribution of species. However the distribution of grassy biomes in Africa cannot be predicted by climate alone, instead interactions between vegetation, climate and disturbance structure the ecosystems. To test if climatic variables, as predicted by an environmental niche model, determine the distribution limits of two common savanna tree species we established a transplant experiment at a range of latitudes and altitudes much broader than the distribution limits of our study species. We planted seedlings of two common savanna trees, Senegalia nigrescens and Colophospermum mopane, at eight paired high and low elevation sites across an 850 km latitudinal gradient in South African savannas. At each site seedlings were planted in both grassy and cleared plots. After 2 years of growth, rainfall, temperature and location inside or outside their distribution range did not explain species success. Grass competition was the only variable that significantly affected plant growth rates across all sites, but grass competition alone could not explain the distribution limit. Species distributions were best predicted when maximum tree growth rates were considered in relation to local fire return intervals. The probability of sapling escape from the fire trap was the most likely determinant of distribution limits of these two species. As trees grew and survived 100 s of kilometers south of their current range limits we conclude that climate alone does not explain the current distribution of these trees, and that climate change adaptation strategies for savanna environments based only on climatic envelope modeling will be inappropriate.